ASOSIASI ANTARA UKURAN PERFORMA AKUNTANSI DAN RETURN SAHAM: SUATU PENGUJIAN TERHADAP HIPOTESIS SIKLUS KEHIDUPAN PERUSAHAAN - Prasetya, Daniel Eka; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 16 No 2 (2016), 2016)
The study aims to test the market response to the accounting performance information as well as the implications of the corporate life cycle theory on it. The data this study is all the company's manufacturing listed on the Indonesian Stock Exchange from 2009 to 2014. The samples were done purposively. The research variables include the cumulative abnormal return as the dependent variable and unexpected earnings, unexpected capital expenditures and sales growth as independent variables. Grouping the company to a company's life cycle by using age, capital expenditure and sales growth as a predictor. Based on the results of statistical tests earnings unexpected have a positive effec on stock returns and responded differently throughout the life cycle of the company. Results of statistical tests appropriate level of the corporate life cycle showed Unexpected capital expenditure and sales growth responded differently throughout the life cycle of the company. The overall study results showed earnings Unexpected, Unexpected capital expenditure and sales growth is a function of the corporate life cycle.
Keywords: life cycle of the company, the size of the accounting performance